Balloon aortic valvuloplasty for severe aortic stenosis as a bridge to transcatheter/surgical aortic valve replacement. Issue 4 (8th November 2012) - Ben‐Dor, Itsik; Maluenda, Gabriel; Dvir, Danny; Barbash, Israel M.; Okubagzi, Petros; Torguson, Rebecca; Lindsay, Joseph; Satler, Lowell F.; Pichard, Augusto D.; Waksman, Ron
<x xml:space="preserve">Abstract</x> Objectives: This study aimed to determine success‐ and complication rates after balloon aortic valvuloplasty (BAV) and the outcome of BAV as a standalone therapy versus BAV as a bridge to transcatheter/surgical aortic valve replacement (T/SAVR). Background: The introduction of transcatheter aortic valve replacement (TAVR) has led to a revival in BAV as treatment for patients with severe aortic stenosis. Methods: A cohort of 472 patients underwent 538 BAV procedures. The cohort was divided into two groups: BAV alone 387 (81.9%) and BAV as a bridge 85 (18.1%) to (n = 65, TAVR; n = 20, surgery). Clinical, hemodynamic, and follow‐up mortality data were collected. Results: There was no significant difference between the two groups in mean age (81.7 ± 8.3 vs. 83.2 ± 10.9 years, P = 0.18), society of thoracic surgeons score (13.1 ± 6.2 and 12.4 ± 6.4, P = 0.4), logistic EuroSCORE (45.4 ± 22.3 vs. 46.9 ± 21.8, P = 0.43), and other comorbidities. The mean increase in aortic valve area was 0.39 ± 0.25 in the BAV alone group and 0.42 ± 0.26 in the BAV as a bridge group, P = 0.33. The decrease in mean gradient was 24.1 ± 13.1 in the BAV alone group vs. 27.1 ± 13.8 in the BAV as a bridge group, P = 0.06. During a median follow up of 183 days [54–409], the mortality rate was 55.2% (n = 214) in the BAV alone group vs. 22.3% (n = 19) in the BAV as a bridge group during a median follow‐up of 378 days [177–690], P < 0.001. Conclusion: In high‐risk patients with aortic stenosis and temporary contraindications to SAVR/TAVR, BAV may be used as a bridge to intervention with good mid‐term outcomes. © 2012 Wiley Periodicals, Inc.